ECOLOGICAL STATUS AT THE KONJSKO LOCALITY OF LAKE PRESPA ACCORDING TO THE ASPT INDEX OF BOTTOM FAUNA COMPOSITION (UKLO Proceedings, 2025)
The Water Framework Directive (EU 2000) identifies macrozoobenthos as an essential component of benthic fauna in aquatic ecosystems, playing a critical role in the assessment of ecological status. This study presents findings from research conducted at the Konjsko locality in Lake Prespa, Republic of North Macedonia. The composition, richness, and diversity of macrozoobenthos were examined during July 2022 and August 2023. Sampling was performed in the Macedonian section of Lake Prespa at the Konjsko locality, adhering to the methodologies outlined in the WFD and ISO standards for macroinvertebrate sampling. A total of eight species across five taxonomic groups from the macrozoobenthos were identified at the Konjsko locality: Oligochaeta, Gastropoda, Bivalvia, Amphipoda, and Insecta. The Gastropoda represented the most diverse group, with three species accounting for 37.5% of the total identified. Oligochaetes comprised the second most diverse group, represented by two species (25%). Bivalvia, Amphipoda, and Insecta each exhibited the lowest density, with only one species per group, constituting 12.5% each of the overall diversity. Notably, the highest population density recorded was for Dreissena carinata, at 875 individuals per square meter at a depth of 2 meters within the Konjsko locality. Based on the findings, the biodiversity and abundance of macrozoobenthos indicate that the Konjsko locality in Lake Prespa possesses a moderate ecological status, as assessed by the Average Score Per Taxon (ASPT) index.